Lipopolysaccharide preconditioning facilitates M2 activation of resident microglia after spinal cord injury. Issue 12 (10th July 2014) - Hayakawa, Kentaro; Okazaki, Rentaro; Morioka, Kazuhito; Nakamura, Kozo; Tanaka, Sakae; Ogata, Toru
<x xml:space="preserve">Abstract</x> The inflammatory response following spinal cord injury (SCI) has both harmful and beneficial effects; however, it can be modulated for therapeutic benefit. Endotoxin/lipopolysaccharide (LPS) preconditioning, a well‐established method for modifying the immune reaction, has been shown to attenuate damage induced by stroke and brain trauma in rodent models. Although such effects likely are conveyed by tissue‐repairing functions of the inflammatory response, the mechanisms that control the effects have not yet been elucidated. The present study preconditioned C57BL6/J mice with 0.05 mg/kg of LPS 48 hr before inducing contusion SCI to investigate the effect of LPS preconditioning on the activation of macrophages/microglia. We found that LPS preconditioning promotes the polarization of M1/M2 macrophages/microglia toward an M2 phenotype in the injured spinal cord on quantitative real‐time polymerase chain reaction, enzyme‐linked immunosorbent assay, and immunohistochemical analyses. Flow cytometric analyses reveal that LPS preconditioning facilitates M2 activation in resident microglia but not in infiltrating macrophages. Augmented M2 activation was accompanied by vascularization around the injured lesion, resulting in improvement in both tissue reorganization and functional recovery. Furthermore, we found that M2 activation induced by LPS preconditioning is regulated by interleukin‐10 gene expression, which was preceded by the transcriptional activation of interferon regulatory factor (IRF)−3, as demonstrated by Western blotting and an IRF‐3 binding assay. Altogether, our findings demonstrate that LPS preconditioning has a therapeutic effect on SCI through the modulation of M1/M2 polarization of resident microglia. The present study suggests that controlling M1/M2 polarization through endotoxin signal transduction could become a promising therapeutic strategy for various central nervous system diseases. © 2014 Wiley Periodicals, Inc.